DUAL MOBILITY CUPS REDUCE DISLOCATION RATE IN TOTAL HIP ARTHROPLASTY FOR DISPLACED FEMORAL NECK FRACTURES - Maksim Zagorov; Kalin Mihov; Svetoslav Dobrilov; Atanas Tabakov; Alexander Gospodinov; Gergana Nenova (Peytchinski Publishing, 2018)
PURPOSE: To assess the dislocation rate after total hip arthroplasty with dual mobility cup (DMC) for displaced femoral neck fractures and to compare the results with that of conventional total hip arthroplasty (THA) and bipolar hemiarthroplasty (BHA) in the same clinical setting at our institution. MATERIALS AND METHODS: 49 cases (47 patients) treated with total hip arthroplasty with DMC, 38 cases (38 patients) with BHA and 29 patients (29 cases) operated on with conventional THA were retrospectively reviewed. RESULTS: In the DMC total hip arthroplasty group, there were no dislocations (0%). %). One dislocation (3,1%) occurred in the BHA group, and 3 dislocations occurred (11,1%) in the THA group. ). There was a statistically significant difference in favour of DMC group compared to THA group regarding dislocation rate (p=0,05). Dislocation rate did not differ significantly between DMC and BHA groups. There was no significant difference in mortality, complications and re-operation rate between groups. CONCLUSION: Dual mobility cups significantly reduce dislocation rate in total hip arthroplasty performed for displaced femoral neck fractures compared to conventional total hip arthroplasty while similar advantage over bipolar hemiarthroplasty could not be demonstrated in the current study.